ENCAPISULATION OF MANGOSTEEN PEEL EXTRACT (GARCINIA MANGOSTANAL.) AS A NARUTAL INHIBITOR FOR SIWALAN SAP (BORASSUS FLABELLIFER) - Siti, Diyah; KHOIR, RIRIN (Department of Biology Education, Faculty of Teacher Training and Education, Universitas Wijaya Kusuma Surabaya, 2025)
Mangosteen fruit (Garcinia mangostana L.) is generally only used for its flesh, approximately ¾ of which becomes waste, while the mangosteen peel has benefits as a natural preservative. This study aims to determine the effect of adding the percentage of encapsulation of mangosteen peel extract as a natural inhibitor of Siwalan sap. This study used a Completely Randomized Design (CRD) with 5 treatments repeated three times. The tests carried out included antioxidant activity, pH, shelf life, and organoleptic tests. Analysis of antioxidant activity and pH test data used ANOVA. If a significant difference is found, continue with the Tukey test. Analysis of shelf life test using linear regression, organoleptic analysis using the Friedman test. Based on the results of the study, it showed that the best treatment was obtained in treatment P5 (encapsulation of 10% mangosteen peel waste extract and 500 ml of Siwalan sap).